Financial Performance Measurement of Manufacturing Companies in Indonesia and Malaysia - Moh. Yudi Mahadianto; Nur Aprianto; Rafi Budiman (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to examine and compare the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX) and Bursa Malaysia from 2021 to 2023, using the Economic Value Added (EVA) and Financial Value Added (FVA) methodologies. This study adopts a descriptive approach, with samples selected through purposive sampling comprising 22 companies from the IDX and 19 companies from Bursa Malaysia within the specified period. The findings of this study serve as a reference for companies and investors in evaluating financial performance through the EVA and FVA approaches. Additionally, the results contribute both theoretically and practically to a deeper understanding of value-added-based performance measurement in the two countries. The study also offers recommendations for enhancing financial management practices and guides potential investors in the manufacturing sector on both exchanges.